Influence of Customer Quality Perception on the Effectiveness of Commercial Stimuli for Electronic Products - Garrido-Morgado, Álvaro; González-Benito, Óscar; Martos-Partal, Mercedes (Frontiers in Psychology, 2016)
Creating and maintaining customer loyalty are strategic requirements for modern business. In the current competitive context, product quality and brand experience are crucial in building and maintaining customer loyalty. Consumer loyalty, which may be classified into cognitive loyalty and affective loyalty, is related to customers’ quality perception. Cue utilization theory distinguishes two dimensions for perceived quality, extrinsic quality –linked to the brand– and intrinsic quality –related with internal product characteristics. We propose that (i) cognitive loyalty is more influenced by intrinsic product quality whereas extrinsic product quality (brand name) is more salient for affective loyalty and, (ii) different commercial stimuli have a differential effectiveness on intrinsic and extrinsic perceived quality. In fact, in this study, we analyze how perceived quality dimensions may influence the effectiveness of two different commercial stimuli: displays and advertising flyers. While displays work within the point of sale under time-constrained conditions where consumers are more likely to use heuristics to simplify their decisions, advertising flyers work outside of the point of sale under low time-constrained conditions, and therefore favor a more reasoned purchase decision where systematic processing will be more likely. We analyze the role of quality perception in determining the effectiveness of both these commercial stimuli for selling products that induce high purchase involvement and perceived risk. The empirical analysis focuses on computer products sold by one of Europe’s largest computer retailers and it combines scanner, observational, and survey data. The results show that both dimensions of quality perceptions moderate the influence of displays and advertising flyers on sales, but their impact is different on each commercial stimuli. Extrinsic quality perception increases to a greater extent the effect of displays due to the use of a brand name heuristic. However, intrinsic quality perception improves to a greater extent the effect of advertising flyers, which in turn are more closely related to systematic decision processing.